Did the Basel Process of Capital Regulation Enhance the Resiliency of European Banks? - Thomas Paul Gehrig; Maria Chiara Iannino (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper analyses the evolution of the resiliency of the European banking sector after the implementation of the Basel Capital Accord. In particular, by analysing SRISK and CoVaR we trace systemic risk and measures of systematic risk as the Basel process unfolds. We observe that, though systematic risk for European banks have been decreasing over the last three decades, systemic risk has heightened especially for the largest systemic banks. While the Basel process has succeeded in containing systemic risk of small banks, it has been less successful for the larger institutions. The latter ones opportunistically exploited the option of self-regulation by employing internal models and effectively increasing SRISK. Hence, the sub-prime crisis found the largest and more systemic banks ill-prepared and lacking resiliency. This condition was even aggravated during the European sovereign crisis.
Keywords: G21; G01; B26; 330